2016
DOI: 10.1016/j.ces.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the carbon chain length of a sulfate-based surfactant on the formation of CO2, CH4 and CO2–CH4 gas hydrates

Abstract: Influence of the carbon chain length of a sulfate-based surfactant on the formation of CO 2 , CH 4 and CO 2 -CH 4 gas hydrates, Chemical Engineering Science, http://dx. AbstractThis study investigates how the length of the carbon chain of homologous surfactants affects the amount and growth rate of gas hydrates formed in quiescent CO 2 /CH 4 /water systems. The 1 Present address: PDVSA Intevep, Los Teques -Edo. Miranda, Apto 76343, Caracas 1070-A, Venezuela 2 hydrate formation experiments were conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 35 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…Ionic surfactants also affect the morphology of the resultant hydrate particle, suggesting that a capillary-driven pattern occurs during hydrate growth when the gas is CH4 and SDS or AOT are present, while a rapid growth of a non-permeable hydrate 'skin' grows in the other cases. The results summarised are consistent with previous observations, 61 -63 including those reported by Dicharry et al, 64 who studied hydrate formation triggered by tetrahydrofuran (THF), where the effect of the alkyl chain length of sodium alkyl sulfates (from 8 to 18 carbon atoms) was studied explicitly. It has been argued that surfactants are not effective in CO2-rich systems because of a competitive adsorption between CO2 and the surfactants at the water-gas interface.…”
Section: Selected Promising Technological Applications Of Gas Hydratessupporting
confidence: 91%
“…Ionic surfactants also affect the morphology of the resultant hydrate particle, suggesting that a capillary-driven pattern occurs during hydrate growth when the gas is CH4 and SDS or AOT are present, while a rapid growth of a non-permeable hydrate 'skin' grows in the other cases. The results summarised are consistent with previous observations, 61 -63 including those reported by Dicharry et al, 64 who studied hydrate formation triggered by tetrahydrofuran (THF), where the effect of the alkyl chain length of sodium alkyl sulfates (from 8 to 18 carbon atoms) was studied explicitly. It has been argued that surfactants are not effective in CO2-rich systems because of a competitive adsorption between CO2 and the surfactants at the water-gas interface.…”
Section: Selected Promising Technological Applications Of Gas Hydratessupporting
confidence: 91%
“…However, experiments conducted with continuous stirring have shown significant gas consumption due to the phase change even with lower THF concentrations [14,16]. Furthermore, the addition of surfactants like sodium alkyl sulfates (C8-C16) along with low mol% THF, helps in faster hydrate nucleation and higher gas uptake [28,29]. Additionally detailed structural studies indicated that the hydrates formed with lesser amounts of THF are crystallised into mixtures of both sI and sII, while the hydrates with stoichiometry crystallise into sII [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1C, LS molecules can adsorb on the surface of forming hydrate particles under the action of hydrogen bonds between partial hydrophilic groups and hydrate molecules. Meanwhile, partial hydrophilic groups, such as sulfonic acid group and carboxyl group, are exposed to the outside surface of forming hydrate particles, which leads to mutual repulsion among forming hydrate particles under electrostatic action (Dicharry et al, 2016). And the hydrate particles become more wettable for water molecules due to hydrophilic groups.…”
Section: Lsmentioning
confidence: 99%